OPAK FAULT DEFORMATION MONITORING USING SENTINEL-1 INSAR DATA FROM 2016-2019 IN YOGYAKARTA INDONESIA - Bondan Galih Dewanto; Mohamad Bagas Setiawan; Gilang Cahya Nusantara (Department of Geodesy Engineering, Faculty of Engineering, Diponegoro University,Indonesia, 2020)
The 2006 Yogyakarta earthquake occurred at 05.55 West Indonesia Time, May 27, 2006 with a magnitude of Mw 5.9. The earthquake had a great trauma effect for the community, because there were many fatalities, around 6,000 people died. Therefore, it is very important to conduct research to determine the deformation that is currently happening around the Opak Fault. In this research, during 2016-2019, we collected products for Sentinel-1 synthetic aperture radar interferometry (InSAR) to measure the current fault deformation. The InSAR data was processed using LiCSBAS, a time series analysis kit of open-source SAR interferometry (InSAR) that integrates with the automated Sentinel-1 InSAR processor (LiCSAR). In the processing scheme for LiCSBAS, interferograms with many unwrapping errors are automatically detected and removed via loop closure. Reliable time series and velocities are extracted using several noise indices with the help of masking. The location of the Opak Fault can be detected clearly in the result because the deformation pattern around the fault is contrary different. The west of Opak Fault shows an uplift movement, while the deformation occurred in east area of the fault shows subsidence movement. Keywords : Opak Fault, Crustal Deformation, Sentinel-1 InSAR Data, LiCSBAS